If it's not what You are looking for type in the equation solver your own equation and let us solve it.
c in (-oo:+oo)
(2/3)*(6*c+4)-(8*c)+5 = 0
(2/3)*(6*c+4)-8*c+5 = 0
2/3*(6*c+4)-8*c+5 = 0
2/3*(6*c+4)-8*c+5 = 0
8/3-4*c+5 = 0
23/3-4*c = 0
23/3-4*c = 0
23/3-4*c = 0 // - 23/3
-4*c = -23/3 // : -4
c = -23/3/(-4)
c = 23/12
c = 23/12
| B-5.6=3.7 | | -23=j-20 | | -2(5a+6)=-33-7a | | -b+2=b-2(b-1) | | 3a+6b=0 | | (12x+6)(13x-1)= | | 7(x+5)-58=18 | | 2x+24=-8-4(2x-8) | | 5e=55 | | 5.9=-A-4.8 | | 2k+3-k=k+2 | | -9=1-6x+2 | | -10/2(-5)= | | 9r=-6 | | x+6=8x-15 | | 7-3x-10=-66 | | -1/6*b=3 | | 4k+3=10-3k | | -3(y+2)=-2(y+4)-y | | -3x^2=1 | | (19x+6)(20x)= | | 0=3x^2+1 | | 5m^2+13m+15=0 | | f(x)=5x^2+10x+1 | | x^3-5x^2-5x-1=0 | | 3y-9y+5w+w= | | c/4+3=8 | | 5-1k=21-3k+12 | | (51x+3)(1+52x)= | | X/8-6=8 | | 5+x/8=-3 | | (x+2x^3-3)/(x-1)=0 |